2013
DOI: 10.2135/cropsci2012.11.0672
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Aphid Biotype 4 Identified

Abstract: The soybean aphid [Aphis glycines Matsumura (Hemiptera: Aphididae)] is an invasive pest of soybean [Glycine max (L.) Merr.]. Since the first report in the United States in 2000 it has become one of the most damaging soybean pests. Three soybean aphid biotypes have been reported to date. The objective of this research was to determine whether an A. glycines field isolate collected near Lomira, WI, was unique from those previously reported. The response of the Lomira isolate was compared to existing soybean aphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 33 publications
(46 reference statements)
0
70
1
Order By: Relevance
“…The Rag1 and Rag2 genes suppressed aphid populations to similar levels in caged settings using biotype-1 soybean aphids OÕNeal 2012, Wiarda et al 2012); therefore, differences in aphid suppression for the Rag1 and Rag2 genes within a given location-year may be due to the presence of virulent biotypes. Virulent soybean aphid biotypes are present in North America (Kim et al 2008, Hill et al 2010, Alt and Ryan-Mahmutagic 2013 and appear to be widespread (Michel et al 2011), but soybean aphids in North America compose one large interbreeding population (Michel et al 2009). Therefore, geographical differences in the efÞcacy of either gene in a particular year may be inconsistent in future years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rag1 and Rag2 genes suppressed aphid populations to similar levels in caged settings using biotype-1 soybean aphids OÕNeal 2012, Wiarda et al 2012); therefore, differences in aphid suppression for the Rag1 and Rag2 genes within a given location-year may be due to the presence of virulent biotypes. Virulent soybean aphid biotypes are present in North America (Kim et al 2008, Hill et al 2010, Alt and Ryan-Mahmutagic 2013 and appear to be widespread (Michel et al 2011), but soybean aphids in North America compose one large interbreeding population (Michel et al 2009). Therefore, geographical differences in the efÞcacy of either gene in a particular year may be inconsistent in future years.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, researchers found virulent populations of soybean aphids that were capable of overcoming either the Rag1 gene (biotype-2), the Rag2 gene (biotype-3), or both genes (biotype-4; Kim et al 2008, Hill et al 2010, Alt and Ryan-Mahmutagic 2013. Notably, these virulent biotypes existed before the commercial release or large-scale planting of any of the Rag genes and therefore, were not selected in response to the use of Rag genes.…”
mentioning
confidence: 99%
“…Given the potential negative effects of chemical use on the environment and human health, host plant resistance is a desirable and sustainable option for the control of soybean aphid (Hill et al, 2012). High yielding soybean cultivars with Rag1 and Rag2 genes are presently available, but the durability of these genes may be in question because aphid biotypes can overcome these resistance genes (Alt and Ryan-Mahmutagic, 2013;Hill et al, 2010;Kim et al, 2008b). High yielding soybean cultivars with Rag1 and Rag2 genes are presently available, but the durability of these genes may be in question because aphid biotypes can overcome these resistance genes (Alt and Ryan-Mahmutagic, 2013;Hill et al, 2010;Kim et al, 2008b).…”
Section: Stability Of Soybean Aphid Resistance In Soybean Across Diffmentioning
confidence: 99%
“…These virulent biotypes are defined by the specific Rag genes on which they can survive. To date, for every Rag gene that has been incorporated into a soybean cultivar either alone or in a combination, a virulent biotype has been found in the USA (Kim et al 2008;Hill et al 2010;Alt and Ryan-Mahmutagic 2013).…”
Section: Introductionmentioning
confidence: 99%